LOCAL LAW WISDOM IN ATTACHING RADICALISM IN THE NAME OF RELIGION - Gelgel, I Putu (Warmadewa Press, 2021)
Harmony between religious communities in Indonesia is now experiencing many problems, many conflicts occur which are actually triggered by religious issues by carrying religious flags and shouting sacred words they carry out actions that are very far from the behavior of a religious person. In handling cases of violence in the name of religion are almost all opinions say that law enforcers are seen as very weak and indecisive. If law enforcement officials remain weak and slow. It is very possible that cases of violence in the name of religion will spread to other areas. Local Law Wisdom has the potential and can contribute to anticipating religious violence in the midst of the current dynamics of socio-cultural change, policy steps in the development of national law need to be designed by Interpreting the Functions and Wisdom of Local Law in anticipating radicalism in the name of religion. Transforming Wisdom Local Law into Legislations related to Religious Issues, integrating, and adapting Local Law Wisdom in resolving Inter-religious Conflicts, and revitalizing Local Law Wisdom in maintaining security, order, and Inter-religious Harmony.